Controle hierárquico e adaptativo para aumento do desempenho operacional de reguladores de tensão em redes elétricas inteligentes - Pereira, Paulo Ricardo da Silva (2014)
The evolution of equipment, new functions and control algorithms, supervisory systems, automation and smart grids offer to utilities numerous conditions for improving the voltage profile and the rational use of its equipment on their networks. To the step voltage regulators, the presence of serial equipment, different loading scenarios and topologies that can arise due to perform maneuvers necessitate a constant review of its settings and operating conditions. The dynamics of operation and mutual influence between regulators brings effects throughout the distribution network. The deficiency of coordination between the equipment can result in violations of voltage levels, consumer complaints and increase in switching regulators. This work presents a hybrid control, operating with individual modules and control at the local level, but integrated into a hierarchical and centralized control that acts according to the topology of the network and operational condition. The individual control (IC), developed from a methodology self-tuning functions and data processing load and strain on the controllers themselves, enables distributed processing of voltage control, sending information to the centralized control through no responses requested via SCADA system when needed. The global control integrated into the SCADA system operates and performs functions of coordination, validation and prioritization, in real time, streamlining the switching equipment, working on timing and assuming their control functions. The adaptive hierarchical voltage control (CHAT), developed in this thesis, was evaluated and compared with conventional operation in various operating scenarios and showed a fast and effective response both regularization voltage under normal operating conditions as in the reconfiguration of network or contingency acting proactively in voltage control of distribution networks.